A comparative study between single layer versus double layer closure in ileostomy reversal - Mittal, Sushil; Singh, Harnam; Singh, Gurpreet; Munghate, Anand; Garg, Anjna; Yadav, Manish (Asian Journal of Medical Sciences, 2014)
Background: Ileal perforation peritonitis is a common surgical emergency in the Indian subcontinent and in tropical countries. Formation of an intestinal stoma is frequently a component of surgical intervention for diseases of the small bowel. The technique for stoma reversal has remained controversial is the use of either one or two layers of sutures for anastomosis. Methods: Sixty patients with ileostomy were taken for study .These patients divided in two groups A and B, 30 each. These patients were taken up for ileostomy closure in single layer (group A) (n-30) &double layer (group B) (n-30). Results: 60 Patients of ileostomy were studied, divided equally in 2 groups, A decreased intra operative time was seen in Group A when compared with Group B with no any significant comparative complication in these groups. Conclusion: Two-layer anastomosis for ileostomy closure offers no definite advantage over single layer anastomosis in terms of postoperative leak and other complications. Single layer ileostomy closure technique is safe, easy to perform and simply to taught. Considering duration of the anastomosis procedure and medical expenses single-layer intestinal anastomosis may prove the choice of procedure for most of the surgeons. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10080 Asian Journal of Medical Sciences Vol.6(2) 2015 44-47